Capacity building for food justice in England: the contribution of charity-led community food initiatives. Issue 5 (4th May 2017) - Kneafsey, Moya; Owen, Luke; Bos, Elizabeth; Broughton, Kevin; Lennartsson, Margi
ABSTRACT: This paper discusses the extent to which charity-led initiatives can contribute to capacity building for food justice in England. The paper draws on evaluations of two projects run by the charity Garden Organic: the Master Gardener Programme, operating a network of volunteers who mentor households, schools and community groups to support local food growing, and the Sowing New Seeds programme, which engages "Seed Stewards" to work with communities to encourage the growing and cooking of "exotic" crops. Based on qualitative data about peoples' motivations for participation and the benefits that are experienced, we interpret these projects as examples of capacity building for food justice. We suggest that whilst currently depoliticised, the "quiet" process of reskilling and awareness raising that occurs through shared gardening projects could have transformative potential for people's relationship with food. Finally, we use our findings to raise critical questions and propose future research about food justice concepts and practices.